Morphological traits of native species with potential for High Andean agroecological processes - Nariño, Colombia - BACCA ACOSTA, PEDRO PABLO (2022)
The intense production systems present in the Andean region have generated serious disturbances to high mountain ecosystems, which provide ecosystem services of great importance such as minerals, flora, and fauna. The study of the native flora through morphological descriptors becomes relevant to characterize and identify the vegetation that could be used in agroecological systems. This could serve as a strategy for the recovery and sustainable use of degraded systems since they promote diversity and responsible use of natural resources. The objective of this research was to determine the foliar morphological patterns that characterize four native shrub species of the High Andean forest: C. arborea; W. mariquitae; V. triphyllum y L. Subseriata. Fifteen qualitative and quantitative morphological leaf descriptors were used. Data were subjected to multivariate analysis of main components and multiple correspondences for quantitative and qualitative variables, respectively. Leaf width and leaf shape were found among the most relevant descriptors for C. arborea; leaf length and main petiole length for L. Subseriata; leaf width and color on the upper leaf side for W. mariquitae; and leaf width and petiole thickness for V. triphyllum. This work contributes to identifying the most relevant morphological traits of four High Andean forest shrub species with potential for the implementation of agroecological systems that contribute to the sustainability of areas disturbed by agricultural actions.